Embedding community based flood risk management in investment a part to whole approach. - Maclean, Rupert (East Asia Working Papers, 2017)
Flash floods and landslides are common in Asia and the Pacific. In July 2017, continuous heavy rainfall led to severe flooding in much of the southern region of the Peoples Republic of China (PRC), affecting more than 14.9 million people in 11 provinces. Community-based schemes have evolved into holistic approaches to managing flood risk, which need to be embedded in investment programs. This paper looks at case studies of pilot practices in community based flood risk management (CBFRM) in the PRC and in Indonesia. It also presents lessons and practical guidelines in developing CBFRM investment projects, particularly highlighting community organization, financing, capacity development, gender and social inclusion, risk management, technology transfer, and cultural norms and values.